Escalating the Recovery of Post-Mining Agricultural Land Degradation Impacts through the Social Functioning of Farming Communities (A Case Study in Dengilo District) - Chandra Bahar Madawi; Dewa Oka Suparwata; Yusriyah Atikah Gobel; Moh Muchlis Djibran (Economics and Digital Business Review, 2026)
This study aims to determine the form of agricultural land damage due to mining activities in Dengilo District, Pohuwato Regency. The research approach used a survey method with a descriptive approach, involving 74 affected farmer respondents. This research was conducted for two months, namely August to September 2025 in Dengilo District, Pohuwato Regency, which is an ex-mining land location with a significant level of agricultural land damage. The results of the study show that mining activities in Dengilo District have caused severe and widespread damage to agricultural land, characterized by decreased soil fertility, degradation of land structure, pollution of irrigation water, and decreased agricultural productivity. These impacts not only disrupt the balance of the ecosystem, but also cause socio-economic losses for the community, especially farmers. Thus, more integrated environmental restoration and management efforts are needed to maintain the sustainability of agriculture and the welfare of local communities